Traditional Liquor and the Law Enforcement: The Role of Bhabinkamtibmas in Polresta Ambon - Ghazy Prima Daffa Ohoirat (Police Studies Review, 2021)
This problem arises based on the background of the high circulation of traditional alcohol and also criminal acts caused by liquor, especially sopi in Salahutu District. With the approach with the community through guidance and counseling by conveying the message of kamtibmas, especially in suppressing the circulation of traditional sopi-type alcohol carried out by bhabinkamtibmas. This study aims to optimize the role of bhabinkamtibmas in carrying out their duties, as well as the factors that influence the role of bhabinkamtibmas in suppressing the circulation of traditional sopi-type alcohol in the jurisdiction of the Salahutu Police, Ambon Police.Concepts and theories for analyzing research focus. The research concept used includes the concept of Community Policing by utilizing FKPM and the active role of the community to suppress the distribution of traditional sopi types of alcohol, the concept of Bhabinkamtibmas in conveying security messages to the community, The theory used includes Management Theory and Theory of Crime Prevention.The systematic research method is a qualitative approach. This type of research is descriptive analytic. Data collection techniques with interviews, observation, and document review. The location is in the Salahutu Police Binmas Unit. Validity by triangulation. Data analysis using interactive model analysis.The results of the study found that the role of Bhabinkamtibmas which was analyzed according to their duties and functions contained in the Republic of Indonesia National Police Regulation Number 1 of 2021 about Polmas has gone well but there are several factors that influence the role of bhabinkamtibmas. Influencing factors are internal factors analyzed with management elements and external factors consisting of social conditions of vulnerability in Salahutu District which are analyzed with crime prevention theory, supporting factors from other functions, cooperation with other agencies and implementation of community service duties according to competence.The conclusion of the implementation of optimizing the role of Bhabinkamtibmas in suppressing the circulation of traditional sopi types of alcohol has been running, but there are several factors, both supporting and inhibiting. Constructive suggestions include suggestions for optimizing the implementation of the use of FKPM and youth organizations in maintaining security and community service and assisting the role of the police in conveying social security messages to the community, improving and maximizing internal and external factors that affect the duties and roles of bhabinkamtibmas in suppressing the circulation of traditional types of alcohol sopi in the jurisdiction of the Ambon Police Salahutu Police .